Physiologic characteristics of leisure alpine skiing and snowboarding - Thiel, C.; Rosenhagen, A.; Roos, L.; Huebscher, M.; Vogt, L.; Banzer, W. (Science and Skiing IV, 2008)
PURPOSE: More than 4.2 Mio people in Germany and 82 Mio persons around the world participate in alpine skiing and snowboarding. However, little is known about the physiological workload during leisure sports like alpine skiing and snowboarding. The aim of this study was to assess the average on-slope cardio-respiratory stress, expressed in relative terms of heart rate (%HRR) and oxygen-uptake (%VO2R).